A study of antibiotic resistance pattern of clinical bacterial pathogens isolated from patients in a tertiary care hospital - Handa, Vishal L.; Patel, Bhoomi N.; Bhattacharya, Dr. Arpita; Kothari, Ramesh K.; Kavathia, Dr. Ghanshyam; Vyas, B. R. M. (Frontiers in Microbiology, 2024)
We investigated antibiotic resistance pattern in clinical bacterial pathogens isolated from in-patients and out-patients, and compared it with non-clinical bacterial isolates. 475 bacterial strains isolated from patients were examined for antibiotic resistance. Staphylococcus spp (148; 31.1%) were found to be the most prevalent, followed by Klebsiella pneumoniae (135; 28.4%), Escherichia coli (74; 15.5%), Pseudomonas aeruginosa (65; 13.6%), Enterobacter spp (28; 5.8%), and Acinetobacter spp (25; 5.2%). Drug-resistant bacteria isolated were extended spectrum-β-lactamase K. pneumoniae (8.8%), E. coli (20%), metallo-β-lactamase P. aeruginosa (14; 2.9%), erythromycin-inducing clindamycin resistant (7.4%) and methicillin-resistant Staphylococcus species (21.6%). Pathogens belonging to the Enterobacteriaceae family were observed to undergo directional selection developing resistance against antibiotics ciprofloxacin, piperacillin-tazobactam, cefepime, and cefuroxime. Pathogens in the surgical ward exhibited higher levels of antibiotic resistance, while non-clinical P. aeruginosa and K. pneumoniae strains were more antibiotic-susceptible. Our research assisted in identifying the drugs that can be used to control infections caused by antimicrobial resistant bacteria in the population and in monitoring the prevalence of drug-resistant bacterial pathogens.